A large ventricular fibroma requiring surgical resection in a symptomatic 3-month-old infant. (16th December 2019) - Marshall, Anderson S.; Dabal, Robert J.; Law, Mark A.
Abstract: Cardiac Fibromas are primary cardiac tumours more common in children than in adults. Surgical intervention is often not required except in the case of limited cardiac output or significant arrhythmia burden. We present a symptomatic 3-month-old infant who had successful surgical intervention for a giant right ventricle fibroma found on prenatal imaging.